HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN PENYESUAIAN DIRI ORANG TUA YANG MEMILIKI ANAK AUTIS - Aziz, Abdul; Fatma, Anne (TALENTA, 2013)
A disruption in childhood who became frightened most mothers today is autism. According Hopes and Harris (in Berkell, 1992), a mother with an autistic child will experience greater stress than mothers with children who have mentalÂ  retardation due to loss of critical interpersonal responses in the autistic children. The purpose of the study The purpose of this study was to determine the relationship between social support to adjustment in mothers of children with autism. And to find out how big the role of social support on adjustment to parents (mothers) of children with autism. The research subject of autistic children who were fostered (in therapy / consultation) in the institution "Ananda Mitra" Colomadu. The research sample is purposive sample because by certain characteristics. These characteristics are: 1) a minimum education level of parents of high school and 3) Domiciled in Surakarta Solo and the surrounding areas. Based on the results of the calculation of analytical techniques obtained Pearson product moment correlation coefficient (rxy) at = 0.573, p = 0.000 (p <0,01). These results indicate there is significant positive correlation between social support to adjustment in mothers of children with autism, because it can be interpreted that the social support variables can be used as predictors (independent variables) to predict or measure the adjustment in mothers of children autism.